Chemical Enhanced Oil Recovery (CEOR) Injection Planning to Obtain the Optimum Development Scenario: A Case Study in TBG Field - Aliefan, Tubagus Adam; Kristanto, Dedi; Swadesi, Boni (Journal of Petroleum and Geothermal Technology, 2025)
Chemical Enhanced Oil Recovery (CEOR), particularly through the use of surfactant and polymer injection, has emerged as one of the most effective tertiary recovery techniques for increasing oil recovery from mature reservoirs. CEOR enhances volumetric and microscopic sweeping efficiency, improving the overall recovery factor (RF). This study focuses on Zone C of the TBG Field, a mature oil field with a current recovery factor below 25%, highlighting its potential for further optimization through CEOR. The field, which began production in 1961 and introduced peripheral water injection in 1995, remains a key candidate for unlocking remaining oil in place. This research integrates primary data, including core analysis, PVT data, and polymer field trial results, with secondary data such as petrophysical properties and production performance. Using dynamic modeling with CMG software, the study evaluates three CEOR injection scenarios to determine the most effective method for improving oil recovery. The scenarios simulated included Baseline Waterflood + Polymer (0.4 PV) and Baseline Waterflood + (Surfactant + Polymer) + (Polymer) (0.2 PV SP + 0.7 PV P). The optimal scenario, involving Baseline Waterflood + (Surfactant + Polymer) + (Polymer), demonstrated an incremental oil recovery of 1.24 MMSTB and a recovery factor improvement of 0.974%. The novelty of this research lies in its integration of polymer field trial data with innovative surfactant-polymer combinations tailored specifically to Zone C's reservoir characteristics. This approach provides a scientifically robust and practical strategy for enhancing oil recovery in challenging reservoir conditions. The study concludes that CEOR is a viable method for mature fields like TBG, offering significant potential for improved oil recovery. Future recommendations include exploring the economic feasibility of the selected injection scenario and ensuring the readiness of surface facilities to support full-scale implementation.